2012
DOI: 10.1080/09718923.2012.11892981
|View full text |Cite
|
Sign up to set email alerts
|

Effective Participative Management: Does It Affect Trust Levels of Stakeholders in Schools?

Abstract: This paper reports the findings of the small-scale study on the effectiveness of participative management (PM) as perceived by parents, learners, teachers, community leaders, members of the school governing body and the principal in one school in the Free State, a province of South Africa. Questionnaires were used to gather data and responses were tabulated using the SPSS. The questionnaires were completed by two hundred and eighty two (282) respondents out of three hundred and twenty (320) issued out, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The term 'stakeholders' refers to certain groups and individuals who have a legitimate interest, or a 'stake', in the continuing effectiveness and success of an institution (37) . In the school context, important stakeholders are parents, teachers, principals and canteen managers (38,39) .…”
mentioning
confidence: 99%
“…The term 'stakeholders' refers to certain groups and individuals who have a legitimate interest, or a 'stake', in the continuing effectiveness and success of an institution (37) . In the school context, important stakeholders are parents, teachers, principals and canteen managers (38,39) .…”
mentioning
confidence: 99%
“…Finally, teacher or subject associations were not supportive to both high and low performing schools. The findings imply that all school stakeholders (including industries) both in low and high performing schools should collaborate; ensuring that the teaching of agriculture is successful (Mokoena, 2012). Head teachers play an integral role in the following: making sure that learners receive quality education (Dibapile, 2012;Isaiah & Nenty, 2012); developing a conducive culture for teaching and learning (Cheruto & Kipkoech, 2011), and providing motivation for individuals in the school (Sapungan & Mondragon, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The positive impact of participatory management on job satisfaction isconfirmed by other authors (Rooney, 1988;Hoerr, 1989;Bernstein, 1993;Daniels & Bailey, 1999;Kim, 2002), however others have found that it also has positive influence on productivity (Levitan & Werneke, 1984;Verma 1995), absenteeism (Eaton & Voos, 1989) and effective supervisor communication (Cooke, 1990 Another line of research was not interested only in the influence of participatory management on employees, but on what are the traits that characterize participatory managers. It is interesting to note that from the identified thirty nine characteristics of managers, the ability to communicate effectively with subordinates was in the top ten most important managerial traits (Hackman & Oldham, 1976;Emmert & Taher, 1992;Voon et al, 2011;Mokoena, 2012).…”
Section: Strategic Planning Is the Deliberate Disciplined Approach Tmentioning
confidence: 99%